Pengaruh Stres Kerja terhadap Cyberloafing dengan Ketidakpuasan Kerja sebagai Variabel Mediasi pada Karyawan Generasi Z Alfamart Kota Ende - Patrisius Ndala Wangge; Avianita Rachmawati; Ernesta Leha (MES Bogor, 2026)
This study aims to examine the effect of job stress on cyberloafing behavior with job dissatisfaction as a mediating variable among Generation Z employees of Alfamart in Ende City. The research employed a quantitative approach using a survey method. Purposive sampling was applied, resulting in 88 respondents. Data were analyzed using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with SmartPLS 4 software. The results indicate that job stress has a positive and significant effect on job dissatisfaction. Job dissatisfaction also has a positive and significant effect on cyberloafing. Meanwhile, job stress shows a significant but negative direct effect on cyberloafing. Mediation analysis reveals that job dissatisfaction significantly mediates the relationship between job stress and cyberloafing. These findings suggest that job dissatisfaction plays a crucial role in explaining cyberloafing behavior arising from job stress. This study provides practical implications for retail management in managing employee stress and job satisfaction to reduce cyberloafing behavior in the workplace.